A diaphragm and a battery
Patent Information
- Application Number
- CN202611132561.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-28
- Publication Date
- 2026-10-09
AI Technical Summary
隔膜作为电池内部正负极之间的隔离层,若电解液与隔膜之间的润湿性较差,隔膜的离子电导率显著下降
[0010]与现有技术相比,本发明提供的隔膜通过在陶瓷涂层中同时引入SiO2和Al2O3作为无机填料,并调控二者的质量比a与隔膜闭孔温度b满足30≤a×b≤200的关系式,能够在保证隔膜耐热安全性的前提下,显著提升电解液对隔膜的浸润性,改善离子电导率和吸液率,降低接触角,从而优化电池的动力学性能和快充能力。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of battery technology, specifically relating to a separator and a battery. Background Technology
[0002] In the manufacturing process of lithium-ion batteries, the wettability of the electrolyte to the separator is one of the key factors determining battery performance. As the separating layer between the positive and negative electrodes inside the battery, poor wettability between the electrolyte and the separator significantly reduces the ionic conductivity of the separator. This reduced ionic conductivity hinders the rapid migration of lithium ions during charging and discharging, directly deteriorating the battery's fast-charging performance (kinetic performance).
[0003] Therefore, improving the wettability of the electrolyte to the separator, enhancing ionic conductivity, and improving the fast-charging performance (kinetics) of lithium-ion batteries are of great significance. Summary of the Invention
[0004] In view of this, the technical problem to be solved by the present invention is to provide a separator and a battery, wherein the electrolyte has good wettability to the separator provided by the present invention, and the obtained separator has good electrical conductivity and good fast charging performance when applied to the battery.
[0005] The present invention provides a diaphragm, comprising a base membrane and a ceramic coating disposed on at least one surface of the base membrane, wherein the composite ceramic coating comprises inorganic fillers, and the inorganic fillers comprise SiO2 and Al2O3;
[0006] The mass ratio of SiO2 to Al2O3 is a; the pore-closing temperature of the diaphragm is b℃;
[0007] a and b satisfy the relationship shown in equation I:
[0008] 30≤a×b≤200 Formula I.
[0009] The present invention also provides a battery comprising the above-described separator.
[0010] Compared with the prior art, the separator provided by the present invention introduces SiO2 and Al2O3 as inorganic fillers in the ceramic coating at the same time, and controls the mass ratio a of the two to satisfy the relationship of 30≤a×b≤200 with the separator pore closing temperature b. This can significantly improve the wettability of the electrolyte to the separator, improve the ionic conductivity and liquid absorption rate, and reduce the contact angle, thereby optimizing the dynamic performance and fast charging capability of the battery. Detailed Implementation
[0011] The present invention provides a diaphragm, comprising a base membrane and a ceramic coating disposed on at least one surface of the base membrane, wherein the composite ceramic coating comprises inorganic fillers, and the inorganic fillers comprise SiO2 and Al2O3;
[0012] The mass ratio of SiO2 to Al2O3 is a; the pore-closing temperature of the diaphragm is b℃;
[0013] a and b satisfy the relationship shown in equation I:
[0014] 30≤a×b≤200 Formula I.
[0015] In this invention, poor wettability of the electrolyte to the ceramic layer affects the battery's kinetics. By adding SiO2 to the ceramic layer, the polarity of SiO2 on the electrolyte is utilized to improve the wettability of the electrolyte to the separator, thereby improving the kinetics. However, if the mass ratio of SiO2 to Al2O3 (a) is too large, the heat resistance of the ceramic layer deteriorates, affecting battery safety. Therefore, battery safety is improved by controlling the pore-closing temperature of the separator. When the calculated value of the formula a×b is too large, it affects battery safety performance; when the calculated value of the formula a×b is too small, it affects kinetics. Therefore, only by controlling the calculated value of a×b between 30 and 200 can good wettability and excellent kinetic performance be obtained while ensuring battery safety.
[0016] In this invention, the calculated value of a×b can be 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95, 100, 105, 110, 115, 120, 125, 130, 135, 140, 150, 160, 170, 180, 190, 200, or any value between 30 and 200.
[0017] In some preferred embodiments of the present invention, 30 ≤ a × b ≤ 100. The calculated value of a × b can be 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95, 100, or any value between 30 and 100.
[0018] In this invention, the mass ratio of SiO2 to Al2O3 is 'a'. The value of 'a' is controlled to range from 1:9 to 4:6, and can be any ratio between 1:9, 1.5:8.5, 2:8, 2.5:7.5, 3:7, 3.5:6.5, 4:6, or 1:9 to 4:6.
[0019] In some preferred embodiments of the present invention, the value range of control 'a' is 2:8 to 3:7, and can be 2:8, 2.5:7.5, 3:7, or any ratio between 2:8 and 3:7.
[0020] By controlling the value of 'a' to a range of 1:9 to 4:6, this invention can ensure the battery's excellent heat resistance and wettability.
[0021] The present invention does not impose any special limitations on the testing method for 'a'. For example, the testing method for 'a' includes the following steps:
[0022] The battery was disassembled under low humidity conditions with RH≤1.3%, the separator was removed, the separator was coated, and EDS surface scanning was performed under an electron microscope to quantify the elemental content of Al and Si.
[0023] In this invention, the method of adjusting 'a' is not limited, and it can be adjusted by controlling the feeding ratio of SiO2 and Al2O3 when preparing the slurry.
[0024] In this invention, the pore-closing temperature b ℃ of the diaphragm is in the range of 120℃~150℃, and can be any value between 120℃, 125℃, 130℃, 135℃, 140℃, 145℃, 150℃, or 120℃~150℃.
[0025] In some preferred embodiments of the present invention, the range of controlled b ℃ is 133℃~140℃, and can be 133, 134, 135, 136, 137, 138, 139, 140, or any value between 133℃ and 140℃.
[0026] This invention ensures the heat resistance of the separator by controlling the temperature of b within the range of 120℃ to 150℃, thereby giving the battery good safety performance.
[0027] The present invention does not impose any special limitations on the testing method for b. For example, the testing method for b includes the following steps:
[0028] The battery was disassembled under low humidity conditions and the separator was removed. The DSC testing procedure is as follows:
[0029] 1. Instrument warm-up and baseline calibration: Power on the DSC instrument and warm it up for at least 30 minutes until it reaches a stable state. Run a blank temperature program to obtain a flat baseline, providing a benchmark for data analysis.
[0030] 2. Place the sample: Place the prepared crucible containing the sample into the sample cell of the instrument, place the empty crucible into the reference cell, and close the furnace lid.
[0031] 3. Set the test method: Set the test conditions in the software, such as heating rate of 10℃ / min, temperature range (e.g., 25℃-250℃), and nitrogen flow rate of 50ml / min.
[0032] 4. Run Test: After confirming that everything is correct, start the test. The instrument will automatically record the heat flow signal during the heating process and generate a DSC heat flow-temperature curve. For polymer membranes, the peak temperature of the endothermic peak is usually taken as the pore-closing temperature.
[0033] In this invention, the method of adjusting b is not limited, and the closed-pore temperature of the diaphragm can be controlled in the following ways:
[0034] 1. By controlling the melting range of the membrane base film, ① polymers with different melting points are mixed ② comonomers are introduced ③ molecular weight distribution is controlled ④ "ultra-wide" melting range is achieved through crosslinking ⑤ multi-layer composite structure: the classic PP / PE / PP three-layer composite film superimposes the narrow melting ranges of different materials;
[0035] 2. Improve the crystallinity of the diaphragm by controlling the stretching process of the diaphragm base membrane. ① By adjusting the stretching ratio and rate, the higher the stretching ratio and rate, the higher the degree of molecular chain orientation, the higher the crystallinity, and thus the higher the pore closing temperature; ② By adjusting the stretching temperature: the higher the stretching temperature, the higher the crystallinity, and thus the higher the pore closing temperature.
[0036] 3. Adjustment by selecting blended polymer base film: ① Mix long-chain branched polyethylene or low-melting-point components into polyethylene; ② Blend high- and low-melting-point polyethylene.
[0037] In this invention, the contact angle of the separator is ≤30°, and can be 10°, 15°, 20°, 25°, 30°, or any value between 10° and 30°, preferably any value between 10° and 20°. By controlling the contact angle of the separator, this invention ensures excellent wettability of the electrolyte to the separator, thereby significantly improving the battery's dynamic performance and fast-charging capability.
[0038] In this invention, the ionic conductivity of the membrane is 0.7~0.8 mS·cm. -1 It can be 0.7, 0.71, 0.72, 0.73, 0.74, 0.75, 0.76, 0.77, 0.78, 0.79, 0.8, or 0.7~0.8 mS·cm. -1 Any value between [the specified values]. This invention achieves a balance between performance and safety by controlling the ionic conductivity of the separator, enabling the battery to meet the fast charging requirements of 3C-5C rates while avoiding safety risks caused by excessive porosity or decreased thermal stability.
[0039] In this invention, the liquid absorption rate of the diaphragm is 175%~400%, preferably 220%~400%. By controlling the liquid absorption rate of the diaphragm, this invention ensures sufficient ion conduction medium, excellent fast charging performance, low DCR and high energy efficiency, and excellent cycle stability.
[0040] In this invention, the thermal shrinkage rate of the diaphragm at 150°C for 1 hour is less than 5%. By controlling the thermal shrinkage rate of the thermal film, this invention ensures that the shrinkage of the diaphragm at 150°C is far less than overhall, guaranteeing isolation between the positive and negative electrodes, preventing short circuits, and improving safety. Overhall is the difference between the width of the diaphragm and the width of the negative electrode. The diaphragm must enclose the negative electrode to prevent short circuits; if the thermal shrinkage value is greater than this difference, a short circuit will occur.
[0041] In this invention, the composite ceramic coating in the diaphragm includes inorganic fillers, namely SiO2 and Al2O3. The particle size Dv50 of the SiO2 is 10-50 nm, and can be any value between 10, 15, 20, 25, 30, 35, 40, 45, 50 nm, or 10-50 nm. In this invention, the specific surface area of the SiO2 is controllable; an extremely high specific surface area can enhance electrolyte wettability.
[0042] The Al2O3 is α-phase alumina with a particle size Dv50 of 100-500 nm. By selecting α-phase alumina with the above-mentioned particle size, this invention can significantly improve heat resistance and enhance the heat resistance of the ceramic skeleton, thereby reducing the thermal shrinkage of the diaphragm.
[0043] In some specific embodiments of the present invention, the composite ceramic coating further includes a dispersant selected from carboxymethyl cellulose (CMC).
[0044] In this invention, the thickness of the composite ceramic coating is 1-5 μm, and can be any value between 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, or 1-5 μm. By controlling the thickness of the composite ceramic coating, this invention ensures that the diaphragm has good heat resistance.
[0045] The porosity of the composite ceramic coating is maintained between 40% and 60%, and can be any value between 40%, 45%, 50%, 55%, 60%, or 40%-60%. This invention, by controlling the porosity of the composite ceramic coating, can ensure ion transport and electrolyte retention, and balance the mechanical strength and thermal stability of the membrane.
[0046] In this invention, the base membrane is selected from polyethylene, polypropylene, or their multilayer composite membranes. The porosity of the base membrane is 40%-55%, and can be any value between 40%, 45%, 50%, 55%, or 40%-55%.
[0047] The present invention does not impose any particular limitation on the preparation method of the diaphragm, as long as a diaphragm with a SiO2 to Al2O3 mass ratio a and a closed-cell temperature b satisfying 30 ≤ a × b ≤ 200 can be obtained. As an exemplary preparation method, it includes the following steps:
[0048] (1) Slurry preparation
[0049] Nano-SiO2 and α-phase Al2O3 were added to deionized water at the target mass ratio, along with a dispersant and a polymer binder. The mixture was stirred until homogeneous to obtain a ceramic coating slurry with a solid content of 10-30 wt%.
[0050] The dispersant is selected from carboxymethyl cellulose (CMC), and the mass of the dispersant accounts for 0.1% to 4% of the solid content of the slurry; the polymer binder accounts for 2% to 5% of the coating mass.
[0051] (2) Selection of base film
[0052] (3) Coating and drying
[0053] The slurry is coated onto at least one surface of the base film using a micro-grooving roller coating, dip coating, or spray coating method, with the coating thickness controlled at 1~5 μm (wet film thickness corresponds to dry film thickness). After drying in an oven at 60~80℃, the diaphragm is obtained by winding.
[0054] The present invention also provides a battery comprising the above-described separator.
[0055] In this invention, the battery further includes a negative electrode sheet. The negative electrode sheet of this invention includes a negative electrode current collector and a negative electrode material layer disposed on at least one surface of the negative electrode current collector. The negative electrode material layer includes a negative electrode material, and the negative electrode material includes a negative electrode active material selected from at least one of graphite and silicon carbide materials.
[0056] The negative electrode material may also include conductive agents, binders, and dispersants.
[0057] This invention does not impose specific limitations on the types of conductive agents, binders, and dispersants in the negative electrode material, and they can be selected according to actual needs. As an example, the conductive agent is one or more of graphite, superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers; the binder is one or more of styrene-butadiene rubber, polyvinylidene fluoride, polytetrafluoroethylene, polyvinyl butyral, waterborne acrylic resin, and carboxymethyl cellulose; the dispersant is selected from sodium carboxymethyl cellulose (CMC) and / or polyvinylpyrrolidone (PVP).
[0058] The present invention does not impose any particular limitation on the negative electrode current collector, as long as it has high conductivity and does not cause adverse chemical changes in the battery. For example, copper, stainless steel, aluminum, nickel, titanium, sintered carbon, copper or stainless steel surface-treated with one of carbon, nickel, titanium or silver, or aluminum-cadmium alloy can be used.
[0059] This invention does not impose any particular limitation on the preparation method of the negative electrode sheet; any preparation method known to those skilled in the art is acceptable. The preparation can be carried out according to the following method:
[0060] The negative electrode active material, binder, conductive agent and dispersant are mixed evenly according to the mass ratio, solvent is added, and the mixture is stirred under vacuum until the system is homogeneous to obtain a negative electrode slurry with a certain solid content; the negative electrode slurry is coated on the surface of the negative electrode current collector and then rolled and cut to obtain a negative electrode sheet.
[0061] The mass ratio of the negative electrode active material, binder, conductive agent and dispersant is 90%-98%: 1.5%-3%: 0.5%-3%: 1%-2%.
[0062] The compaction density of the negative electrode sheet is 1.55-1.75 g / cm³. 3 It can be 1.55 g / cm³. 3 1.6 g / cm 3 1.65g / cm 3 1.7 g / cm 3 1.75 g / cm 3 or 1.55-1.75 g / cm³ 3 Any value between; the areal density of the negative electrode is 160~250 g / m³. 2 It can be 160 g / m 2 170 g / m 2 180 g / m 2 190 g / m 2 200 g / m 2 210 g / m 2 220 g / m 2 230 g / m 2 240 g / m 2 250 g / m 2 or 160~250g / m 2 Any value between.
[0063] The battery provided by the present invention further includes a positive electrode sheet, which includes a positive current collector and a positive electrode material layer composited on the surface of the positive current collector.
[0064] The positive electrode material layer includes a positive electrode material, and the positive electrode material includes a positive electrode active material. In this invention, the positive electrode active material includes at least one of lithium iron phosphate (LFP), lithium manganese iron phosphate (LFMP), nickel cobalt manganese / nickel cobalt aluminum (NCM / NCA), lithium cobalt oxide (LCO), and lithium manganese oxide (LMO).
[0065] In this invention, the positive electrode active material layer further includes a binder, a conductive agent, and a dispersant.
[0066] The binder is used to improve the adhesion between the positive electrode active material particles and the adhesion between the positive electrode active material and the current collector. Therefore, the binder suitable for use in the embodiments is a fluorinated polyolefin binder, which may include, but is not limited to, polyvinylidene fluoride (PVDF), PVDF copolymers, or their modified (e.g., modified with carboxylic acid, acrylic acid, acrylonitrile, etc.) derivatives.
[0067] In this invention, a conductive agent is used to provide conductivity in the electrode. The conductive agent used in this invention can be any conductive agent without particular limitation, as long as it has suitable electronic conductivity and does not cause adverse chemical changes in the battery. Preferably, the conductive agent includes one or more of carbon black, graphite, carbon nanotubes, and graphene; the carbon black includes acetylene black (AB), Super P (conductive carbon black), and Ketjenblack; the graphite includes natural graphite and artificial graphite; the artificial graphite includes KS-6; the carbon nanotubes include single-walled carbon nanotubes (SWCNTs) and multi-walled carbon nanotubes (MWCNTs); and the graphene includes graphene oxide (GO), reduced graphene oxide (rGO), and graphene nanosheets (GNPs).
[0068] The dispersant is used to improve the uniformity and stability of the slurry, ensuring that the positive electrode active material, conductive agent, and binder are uniformly dispersed in the solvent, avoiding agglomeration or sedimentation, thereby improving the electrochemical performance of the electrode. In this invention, the dispersant is selected from one or more of acrylic acids, acrylates, polyether esters, phosphate esters, small molecule alkanolamines, polyurethanes, modified styrene / maleic anhydride, hydrogenated nitrile butadiene rubber (HNBR), polyvinylpyrrolidone (PVP), and polyethylene glycol (PEG).
[0069] In this invention, the positive electrode active material constitutes the main material, and the mass ratio of the main material, conductive agent, binder and dispersant is 94.5~98.5:0.5~1.5:1~2:0~2.
[0070] This invention does not impose any particular limitation on the preparation method of the positive electrode sheet; any preparation method known to those skilled in the art is acceptable. The preparation can be carried out according to the following method:
[0071] The positive electrode active material, binder, conductive agent and dispersant are mixed evenly according to the mass ratio, solvent is added, and the mixture is stirred under vacuum until the system is homogeneous to obtain a positive electrode slurry with a certain solid content; the positive electrode slurry is coated on the surface of the positive electrode current collector and then rolled and cut to obtain a positive electrode sheet.
[0072] The present invention does not have any particular limitation on the type of solvent, which can be N-methylpyrrolidone (NMP).
[0073] The solid content of the positive electrode slurry is 50%-70%, and can be any value between 50%, 55%, 60%, 65%, 70%, or 50%~70%.
[0074] The final positive electrode sheet has an areal density of 300-460 g / m². 2 The compacted density is 2.65-4.2 g / cm³. 3 .
[0075] The areal density and compaction density of the positive electrode vary depending on the type of positive electrode active material. For example,
[0076] When the positive electrode active material is LFP, the areal density is 300-360 g / m³. 2 The compacted density is 1.95-2.6 g / cm³. 3 ;
[0077] When the positive electrode active material is NCM, the areal density is 400-460 g / m³. 2 The compacted density is 3.45-3.9 g / cm³. 3 ;
[0078] When the positive electrode active material is LMO, the areal density is 380-420 g / m³. 2 The compacted density is 2.65-3.7 g / cm³. 3 ;
[0079] When the positive electrode active material is LCO, the compaction density is 3.6-4.2 g / cm³. 3 .
[0080] In this invention, there is no particular limitation on the type of positive current collector. For example, the current collector can be a metal foil or a composite current collector.
[0081] Specifically, the metal foil can be aluminum or an aluminum alloy;
[0082] Specifically, the composite current collector includes an intermediate high-molecular layer and metal layers disposed on both sides of the polymer layer. The polymer layer includes polymer materials, including at least one of polyamide (PA), polyterephthalate, polyimide (PI), polyethylene (PE), polypropylene (PP), polystyrene, polyvinyl chloride (PVC), aramid, acrylonitrile-butadiene-styrene copolymer (ABS), polybutylene terephthalate (PET), poly(p-phenylene terephthalamide) (PPTA), polypropylene, polyoxymethylene (POM), epoxy resin, phenolic resin, polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), silicone rubber, polycarbonate (PC), polyvinyl alcohol (PVA), polyethylene glycol (PEG), cellulose, starch, protein, their derivatives, their crosslinks, and their copolymers. The metal layer may include at least one of aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy.
[0083] The battery provided by this invention also includes an electrolyte. The electrolyte of this invention can be any electrolyte suitable for electrochemical energy storage devices in the art.
[0084] In this invention, the viscosity of the electrolyte is in the range of 2~5 mPa·s, and can be 2 mPa·s, 2.5 mPa·s, 3 mPa·s, 3.5 mPa·s, 4 mPa·s, 4.5 mPa·s, 5 mPa·s, or any value between 2 and 5 mPa·s. When the viscosity of the electrolyte exceeds the above range, it affects the wetting effect on the negative electrode of the battery, thereby affecting the film formation effect, resulting in a rougher SEI film and an increase in the roughness of the electrode sheet.
[0085] In this invention, the electrolyte comprises an electrolyte, a solvent, and additives. The electrolyte typically includes a lithium salt.
[0086] Specifically, the lithium salt includes at least one selected from lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalate borate (LiDFOB), lithium dioxalate borate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorodioxalate phosphate (LiDFOP), and lithium tetrafluorooxalate phosphate (LiTFOP). The concentration of the electrolyte in the electrolyte solution can be 0.5~5 mol / L.
[0087] The solvent is selected from at least one of ethylene carbonate, propylene carbonate, methyl ethyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butyl carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, sulfolane, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone, acetonitrile, dimethyl glycol ether (DME), dimethyl propylene glycol ether (PGME), and tetrahydrofuran. The solvent accounts for 70%-90% of the mass of the electrolyte.
[0088] The additives can be negative electrode film-forming additives, positive electrode film-forming additives, or additives that can improve certain battery performance, such as additives that improve battery overcharge performance, additives that improve battery high-temperature performance, additives that improve battery low-temperature performance, etc.
[0089] Specifically, positive electrode film-forming additives include: anisole derivatives, polymeric monomers (such as xylene and phenylcyclohexane), and boron / nitrogen heterocyclic compounds (such as LiBOB).
[0090] Negative electrode film-forming additives: vinylene carbonate (VC), fluoroethylene carbonate (FEC), vinyl ethylene carbonate (VEC), 1,3-propanesulfonate lactone (1,3-PS), vinyl sulfite (ES), and vinyl sulfate (DTD). The content of these additives in the electrolyte ranges from 0.1% to 5%, and can be any value between 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5%, or 0.1% to 5%.
[0091] The present invention also provides an electronic device comprising the battery described above. The electrochemical device serves as the power source for the electronic device.
[0092] The electronic device refers to any device that can utilize electrical energy and convert it into mechanical energy, thermal energy, light energy, or one or more other energy forms, such as electric motors, electric heaters, and electric light sources. Specifically, it can include, but is not limited to, mobile devices, electric vehicles, electric trains, ships and satellites, and energy storage systems. Mobile devices can include mobile phones, laptops, drones, robot vacuum cleaners, e-cigarettes, etc.; electric vehicles can include pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.
[0093] To further understand the present invention, the diaphragm and battery provided by the present invention will be described below with reference to the embodiments. The scope of protection of the present invention is not limited by the following embodiments.
[0094] Example 1:
[0095] (1) Preparation of positive electrode:
[0096] LFP positive electrode active material, polyvinylidene fluoride (PVDF), a composite conductive agent of carbon black and conductive graphite in a mass ratio of 1:1, and sodium carboxymethyl cellulose (CMC) were mixed evenly in a mass ratio of 96.8%:2%:1%:0.2% and dispersed in NMP to obtain a positive electrode slurry. The positive electrode slurry was coated onto aluminum foil to obtain a double-sided coated positive electrode sheet. After rolling and cutting, the positive electrode sheet was obtained. The aluminum foil surface was coated with a carbon layer with a thickness of 2 μm.
[0097] The areal density of the positive electrode is 387 g / m³. 2 Compacted density: 2.55 g / cm³ 3 .
[0098] (2) Preparation of negative electrode:
[0099] Graphite, styrene-butadiene rubber (SBR), conductive carbon black, and sodium carboxymethyl cellulose (CMC) were mixed uniformly in a mass ratio of 96.4%:0.6%:1.8%:1.2% and dispersed in deionized water to obtain a negative electrode slurry. This negative electrode slurry was then coated onto copper foil to obtain a double-sided coated electrode sheet. After rolling and cutting, the negative electrode sheet was obtained with an areal density of 180 g / m³. 2 Compacted density: 1.6 g / cm³ 3 .
[0100] (3) Preparation of electrolyte:
[0101] Ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) were mixed in a volume ratio of 1:1:1 to obtain an organic solvent. Then, thoroughly dried lithium salt LiPF6 was dissolved in the mixed organic solvent to prepare an electrolyte with a concentration of 1 mol / L. The organic solvent contained 1% fluoroethylene carbonate (FEC) and 2% vinylene carbonate (VC).
[0102] (4) Preparation of the diaphragm:
[0103] Hydrophilic SiO2 nanoparticles with a particle size of 20 nm and α-phase Al2O3 ceramic particles with a particle size of 300 nm were mixed at a mass ratio of 2:8 to prepare an aqueous dispersion with a solid content of 10%. Carboxymethyl cellulose (CMC, accounting for 0.5% of the slurry's solid content) and a polymer binder (sulfonated polyetheretherketone SPEEK aqueous solution, with a solid content of 5%, and a dry weight ratio of mixed powder to SPEEK of 95:5) were added. The mixture was vigorously stirred at 40°C for 2 hours to obtain a uniform ceramic coating slurry.
[0104] HDPE base film with a closed-cell temperature of 140℃ (9 μm thickness, melting range 130-136℃) was selected. The above slurry was coated onto one side of the base film using a micro-gravure roller coating method, and the wet film thickness was controlled at 11.5 μm. After coating, it was dried in an oven at 80℃ and then wound up to obtain a composite separator with a coating thickness of approximately 2.5 μm.
[0105] (5) Assembly and formation:
[0106] The positive electrode, separator, and negative electrode are stacked in sequence, with the separator positioned between the positive and negative electrodes to provide isolation. The cells are then wound to obtain a bare cell. The bare cell is placed in an outer packaging shell, dried, and then injected with electrolyte. After vacuum sealing, settling, formation, and shaping processes, a lithium-ion battery is obtained.
[0107] Examples 2-16 and Comparative Examples 1-4
[0108] Examples 2-16 and Comparative Examples 1-4 each provide a lithium-ion battery. The preparation method is similar to that of Example 1, except that the process parameters involved are different. See Table 1 for details.
[0109] The diaphragm samples used in the following test methods were all prepared according to the following methods:
[0110] Disassemble the battery in a low-humidity or glove box environment and remove the separator.
[0111] Test items:
[0112] 1. The test method for the contact angle of the diaphragm refers to the standard ISO 15989 or GB / T 30693-2014, as follows:
[0113] The static droplet method was employed, using an optical contact angle meter. The diaphragm sample was horizontally fixed on the sample stage. In an inert atmosphere glove box at 25±1℃, 2-5 μL of electrolyte was dropped onto the diaphragm surface using a microsyringe. The droplet profile was recorded using an optical system, and the contact angle was calculated using the Young-Laplace equation. At least three different locations were measured for each sample, and the arithmetic mean was taken as the final contact angle. The electrolyte composition was a mixed solvent of ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) in a volume ratio of 1:1:1, with a lithium salt (LiPF6) concentration of 1 mol / L.
[0114] 2. Method for testing the conductivity of the diaphragm:
[0115] EIS test.
[0116] 3. The absorbance rate is determined according to the standard GB / T 36363-2018, and the following method is used:
[0117] Take a membrane sample dried to constant weight and record the weight as m0; immerse the membrane in standard electrolyte (1 mol / L LiPF6 in EC / EMC / DEC, volume ratio 1:1:1) in an argon atmosphere glove box for 2 hours; after removal, use filter paper to absorb excess electrolyte on the surface and quickly weigh it as m1; calculate the liquid absorption rate according to the following formula: liquid absorption rate = (m1-m0) / m0×100%.
[0118] 4. The reference standard for the heat shrinkage rate of the diaphragm at 150℃ for 1 hour is GB / T 36363-2018, and the test method is as follows:
[0119] Cut the diaphragm into 100 mm × 100 mm samples along both the longitudinal (MD) and transverse (TD) directions, and measure the original dimension L0. Place the sample in a 150℃ constant temperature oven for 1 hour. After cooling to room temperature, measure the dimension L1 again. Calculate the heat shrinkage rate using the following formula: Heat shrinkage rate = (L0 - L1) / L0 × 100%. Test in both the MD and TD directions, and take the larger value as the final result. Test at least 3 samples for each sample and take the average value.
[0120] 5. The particle size of SiO2 was tested using ISO 13320 (laser diffraction method).
[0121] 6. The particle size of Al2O3 was measured using ISO 13320 (laser diffraction method). SiO2 and Al2O3 have different morphologies under an electron microscope: SiO2 is spherical or near-spherical, while Al2O3 is plate-like. The finished product was directly tested using an electron microscope at high magnification.
[0122] 7. Test method for the thickness of the composite ceramic coating: micrometer. The coating thickness is equal to the thickness of the coated diaphragm minus the thickness of the base film.
[0123] 8. The porosity test method for the composite ceramic coating is: ISO 15901-2:2006 Porosity and pore size distribution test (mercury porosimetry).
[0124] 9. Test method for the porosity of the base membrane: ISO 15901-2:2006 Porosity and pore size distribution test (mercury porosimetry).
[0125] 10. DCR Test:
[0126] The HPPC (Hybrid Pulse Power Characterization) method is currently the most widely used DCR test method, GB / T 31486-2015.
[0127] 11. Security:
[0128] Heating test: Reference standard: GB 38031-2025 "Safety requirements for power batteries for electric vehicles".
[0129] Test conditions: The state of charge (SOC) of the battery under test is 100% (charge the battery at a constant current of 0.33 C to the upper limit voltage of 3.65 V, and then charge it at a constant voltage of 3.65 V to the cutoff current of 0.05 C to obtain a battery with 100% SOC); the test environment temperature is room temperature (20-25℃); the temperature control accuracy of the constant temperature chamber is ±2℃.
[0130] Test procedure: Place the 100% SOC battery cells in a constant temperature chamber and heat them to the target temperature (150℃) at a heating rate of 5℃ / min ± 2℃ / min, and hold for 30-60 minutes. During the holding period, continuously monitor the changes in battery cell voltage, surface temperature, and appearance.
[0131] Judgment criteria: If the battery does not catch fire, explode, or leak during the entire heating and heat preservation process, it is considered to have passed the test. The GB 38031-2025 standard requires that the battery cell not catch fire or explode within 30 minutes at 130℃±2℃.
[0132] Table 1
[0133]
[0134]
[0135]
[0136]
[0137] The lithium-ion batteries prepared in the various embodiments of the present invention have good safety performance and have all passed the safety performance test. Furthermore, their fast charging performance is all >65%, which shows that the lithium-ion batteries of the present invention have both good safety performance and fast charging performance.
[0138] From Examples 1-5 and Examples 12-13 compared to Examples 6-11, Examples 14-16 and Comparative Examples 1-4, it can be seen that when a and b meet the parameter ranges defined by the present invention, the safety performance and fast charging performance of the lithium-ion battery are relatively better.
[0139] From Examples 1-5 and Examples 6-7, it can be seen that when the battery satisfies 30≤a×b≤200, the safety performance and fast charging performance of the lithium-ion battery are relatively higher.
[0140] The results of Comparative Examples 1 to 4 show that when the battery does not meet the range of 30≤a×b≤200, the lithium-ion battery has high internal resistance and poor cycle performance.
[0141] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A diaphragm, characterized in that, The composite ceramic coating includes a base film and a ceramic coating disposed on at least one surface of the base film, wherein the composite ceramic coating includes inorganic fillers, and the inorganic fillers include SiO2 and Al2O3. The mass ratio of SiO2 to Al2O3 is a; the pore-closing temperature of the diaphragm is b℃; a and b satisfy the relationship shown in equation I: 30≤a×b≤200 Formula I.
2. The diaphragm according to claim 1, characterized in that, 30≤a×b≤100.
3. The diaphragm according to claim 1, characterized in that, The range of a is 1:9 to 4:
6.
4. The diaphragm according to claim 1, characterized in that, b ℃ ranges from 120℃ to 150℃.
5. The diaphragm according to claim 1, characterized in that, The contact angle of the diaphragm is ≤30°.
6. The diaphragm according to claim 1, characterized in that, The ionic conductivity of the membrane is 0.7~0.8 mS·cm. -1 .
7. The diaphragm according to claim 1, characterized in that, The liquid absorption rate of the diaphragm is >175%.
8. The diaphragm according to claim 1, characterized in that, The thermal shrinkage rate of the diaphragm at 150°C for 1 hour is less than 5%.
9. The diaphragm according to claim 1, characterized in that, The particle size Dv50 of the SiO2 is 10-50 nm.
10. The diaphragm according to claim 1, characterized in that, The Al2O3 is α-phase alumina with a particle size of 100-500 nm.
11. The diaphragm according to claim 1, characterized in that, The composite ceramic coating also includes a polymer binder, which is a water-soluble or water-dispersible polymer with strong anionic functional groups in its side chains.
12. The diaphragm according to claim 1, characterized in that, The polymer binder is a water-soluble or water-dispersible polymer with sulfonate or carboxylate groups in its side chains.
13. The diaphragm according to claim 1, characterized in that, The polymer binder is a sulfonated polyether ether ketone, sodium polystyrene sulfonate, a sulfonic acid-modified acrylate copolymer, or an emulsion synthesized using a reactive sulfonic acid-based emulsifier.
14. The diaphragm according to claim 1, characterized in that, The amount of the polymer binder added accounts for 2%-5% of the mass percentage of the composite ceramic coating.
15. The diaphragm according to claim 1, characterized in that, The composite ceramic coating also includes a dispersant selected from carboxymethyl cellulose (CMC).
16. The diaphragm according to claim 1, characterized in that, The thickness of the composite ceramic coating is 1-5 μm.
17. The diaphragm according to claim 1, characterized in that, The porosity of the composite ceramic coating is maintained at 40%-60%.
18. The diaphragm according to claim 1, characterized in that, The base film is selected from polyethylene (PE), polypropylene (PP) or its multilayer composite film.
19. The diaphragm according to claim 1, characterized in that, The porosity of the base membrane is 40-55%.
20. A battery, characterized in that, Includes the diaphragm as described in any one of claims 1 to 19.
21. The battery according to claim 20, characterized in that, It also includes a negative electrode sheet, which includes a current collector and a negative electrode material layer composited on the surface of the current collector. The negative electrode material layer includes a negative electrode active material, a binder, and a dispersant.
22. The battery according to claim 20, characterized in that, It also includes a positive electrode sheet, which includes a current collector and a positive electrode material layer composited on the surface of the current collector. The positive electrode material layer includes a positive electrode active material, a binder, and a dispersant.
23. The battery according to claim 20, characterized in that, It also includes an electrolyte, which comprises an electrolyte, additives, and a solvent.